Evaluation of the efficiency of highly realistic simulation during the selection of ALV parameters in ARDS - K. A. Tsygankov; I. N. Grachev; V. I. Shatalov; A. V. Shchegolev; E. Yu. Strukov (Вестник анестезиологии и реаниматологии, 2023)
The objective wasto evaluate the efficiency of the highly realistic simulator “Test Chest” in training residents in the specialty “Anesthesiology and Resus-citation” in the alveolar recruitment maneuver and the de-escalation option for setting positive end-expiratory pressure in ARDS during a practical session.Materials and methods. The study included 28 residents of the first year of study in the specialty «Anesthesiology and Resuscitation», who  were divided into two groups. The 1st group – residents who were given theoretical classes before the study: lectures and a seminar on the topic:  «Respiratory support in ARDS» and the 2nd group (simulation) – in addition to the lectures, the trainees had preliminary practical classes in the  simulation center with a demonstration of the method of selecting ALV parameters in ARDS and independent performance of the alveolar recruit[1]ment maneuver, setting the positive pressure at the end of exhalation. In the simulation center, students were offered a situational task, the solution  of which involved determining the clinical picture and selecting the necessary ALV parameters. The evaluation was carried out by two teachers  independently using a checklist modified for objective student evaluation.Results. In the 1st group, 4 (28%) trainees coped with the task, in the 2nd group, in 13 cases (95%), the task was successfully completed. In the course  of the study, the trainees of both groups revealed difficulties in selecting ALV parameters in ARDS, which required a more detailed consideration  of these issues, both in theoretical and practical classes. Conclusion. The use of the highly realistic simulator “Test Chest” in the selection of ALV parameters in ARDS during a practical session makes it  possible to increase the effectiveness of training in the alveolar recruitment maneuver and the de-escalation option for setting positive end-expiratory  pressure in ARDS for residents in the specialty “Anesthesiology and resuscitation”.